ANALISIS PEMASARAN BAWANG GORENG PADA INDUSTRI RUMAH TANGGA FLAMBOYAN DI KELURAHAN PANAU KECAMATAN TAWAELI KOTA PALU - Hasanuddin,Hj.Hadayani, Asfiana (AGROTEKBIS, 2015)
This study aims was to determine the of marketing channels, the magnitude of the marketing margin and determine the efficiency of marketing at the home industry Flamboyan in Panau Village Tawaeli Subdistrict Palu City. The research was conducted at the home industry Flamboyan in Panau Village Tawaeli Subdistrict Palu City. The number of respondents in this study as many as 14 people consisting of on 1 person leaders, 4 person employee, 1 person retailers and 8 person consumer. Determination of the respondents in the management, employees and consumers in the industry Flamboyan in do (purposive while determining the respondents retailers in do (tracing sampling method). Based on the results of research that there are two existing marketing channels in Home Industry Flamboyan namely : Channel I : Producer - Retailers - Consumer Channel II : Producer-Consumer. Total marketing margin on the first line of Rp 105,000 with the following details for the packaging of 100 grams of Rp 20,000 , 150 grams of Rp 35,000 and Rp 50,000 packs of 250 grams. The second marketing channel marketing margins can not be found because there is no marketing agencies involved in marketing products Flamboyan fried onions . The efficiency values of the first channel marketing was 50%  and for the second channel was 0%, which is more efficient marketing channel is the second channel II.